Integration of ozone with co-immobilized microalgae-activated sludge bacterial symbiosis for efficient on-site treatment of meat processing wastewater. (1st May 2021) - Hu, Xinjuan; Meneses, Yulie E.; Stratton, Jayne; Lau, Soon Kiat; Subbiah, Jeyamkondan
Abstract: Direct discharge of high concentration meat processing wastewater (MPW) into municipal sewage system will cause serious shock loading and reduce wastewater treatment efficiency, thus, efficient on-site pretreatment is usually required. Purpose of this study is to integrate ozone with microalgal biotreatment to achieve effective removal of both organic compounds and nutrients with one-step biodegradation and obtain high quality effluent dischargeable to municipal sewage system. Results showed that ozone pretreatment removed 35.0–90.2% color and inactivated 1.8–4.7 log CFU/mL bacteria in MPW. In post biotreatment using microalgae co-immobilized with activated sludge (ACS) bacteria, bacterial growth in ozone pretreated wastewater (7.1–8.1 log CFU/mL) were higher than non-pretreated control (6.0 log CFU/mL) due to enhanced biodegradability of wastewater pollutants. Algal biomass growth in wastewater pretreated with 0.5 (2489.3 mg/L) and 1 (2582.0 mg/L) minute's ozonation were improved and higher than control (2297.1 mg/L). Ozone pretreatment significantly improved nutrients removal. Following ozone pretreatment of 0.5 min, microalgal biotreatment removed 60.1% soluble chemical oxygen demand (sCOD), 79.5% total nitrogen (TN) and 91.9% total phosphate (PO4 3− ) which were higher than control (34.4% sCOD, 63.4% TN, 77.6% total PO4 3− ). Treated effluent contained 342.3 mg/L sCOD, 28.8 mg/L TN, 9.9 mg/L total PO4 3− and could be discharged into municipal sewage system. However, excessive ozone pretreatment displayed adverse impact on algal growth and sCOD removal. Therefore, integration of 0.5 min's ozone pretreatment with microalgae-based biotreatment is an efficient on-site treatment to simultaneously remove organic compounds and nutrients with one-step biodegradation. Highlights: Integration of ozone with microalgae was an effective on-site wastewater treatment. With one-step biotreatment, effluent was dischargeable in municipal sewage system. Excessive ozone treatment of 3 and 5 min adversely affected algal growth.